Baroreflex regulation affects ventilation in the cururu toad Rhinella schneideri - Zena, Lucas A. [UNESP]; Silva, Glauber S. F. da [UNESP]; Gargaglioni, Luciane H. [UNESP]; Bicego, Kenia C. [UNESP] (Company Of Biologists Ltd, 2016)
Anurans regulate short-term oscillations in blood pressure through changes in heart rate (f(H)), vascular resistance and lymphatic f(H). Lung ventilation in anurans is linked to blood volume homeostasis by facilitating lymph return to the cardiovascular system. We hypothesized that the arterial baroreflex modulates pulmonary ventilation in the cururu toad Rhinella schneideri, and that this relationship is temperature dependent. Pharmacologically induced hypotension (sodium nitroprusside) and hypertension (phenylephrine) increased ventilation (25 degrees C: 248.7 +/- 25.7 ml kg(-1) min(-1); 35 degrees C: 351.5 +/- 50.2 ml kg(-1) min(-1)) and decreased ventilation (25 degrees C: 9.0 +/- 6.6 ml kg(-1) min(-1); 35 degrees C: 50.7 +/- 15.6 ml kg(-1) min(-1)), respectively, relative to control values from Ringer solution injection (25 degrees C: 78.1 +/- 17.0 ml kg(-1) min(-1); 35 degrees C: 137.7 +/- 15.5 ml kg(-1) min(-1)). The sensitivity of the ventilatory response to blood pressure changes was higher during hypotension than during hypertension [25 degrees C: -97.6 +/- 17.1 versus -23.6 +/- 6.0 breaths min(-1) kPa(-1); 35 degrees C: -141.0 +/- 29.5 versus -28.7 +/- 6.4 breaths min(-1) kPa(-1), respectively; negative values indicate an inverse relationship between blood pressure and ventilation (or breathing frequency), i.e. as blood pressure increases, ventilation decreases, and vice versa], while temperature had no effect on these sensitivities. Hyperoxia (30%; 25 degrees C) diminished ventilation, but did not abolish the ventilatory response to hypotension, indicating a response independent of peripheral chemoreceptors. Although there are previous data showing increased f(H) baroreflex sensitivity from 15 to 30 degrees C in this species, further increases in temperature (35 degrees C) diminished fH baroreflex gain (40.5 +/- 5.62 versus 21.6 +/- 4.64% kPa(-1)). Therefore, besides an involvement of pulmonary ventilation in matching O-2 delivery to demand at higher temperatures in anurans, it also plays a role in blood pressure regulation, independent of temperature, possibly owing to an interaction between baroreflex and respiratory areas in the brain, as previously suggested for mammals.
Keywords: Baroreceptors; Chemoreceptors; Lung ventilation; Hyperoxia; Autonomic blockade; Anuran amphibians